PERBANDINGAN HUKUM TINDAK PIDANA PERKOSAAN BERDASARKAN PASAL 285 DAN 286 KUHP INDONESIA DENGAN ARTICLE 177 DAN 178 PENAL CODE OF JAPAN (ACT NO. 45 OF 1907): Comparison of Rape of ense Based on Article 285 and 286 of the Indonesia Penal Code with Article 177 and 178 of the Penal Code of Japan (Act No. 45 of 1907) - Puspitasari, Monica Dwi Anny; Multiwijaya, Vientje Ratna (Faculty of Law, Universitas Trisakti, 2024)
Comparative Criminal Law is a way to compare the similarities and dif erences based on the arrangements and elements of the crime of rape in both Indonesia and Japan. The main issues are (1) How is the regulation of the crime of rape according to Articles 285 and 286 of the Indonesian Criminal Code with Articles 177 and 178 of the Penal Code of Japan (Act No. 45 of 1907)? and (2) What are thesimilarities and dif erencesin the elements of the crime of rape according to Articles 285 and 286 of the IndonesianCriminal Code and Articles 177 and 178 of the Penal Code of Japan (Act No. 45 of 1907)?This study uses a comparative normative research method that is descriptive analysis in nature, using secondary data obtained from a literature study which is processed qualitatively with the conclusions that are (1) Regulations in Japan according to Articles 177 and 178 are only limited to crimes against decency, rape andbigamy while regulation in Indonesia is divided into attacking obscenity, and traf icking of women and children. (2) There are similarities in the two arrangements, namely that they are formal of enses, elements of violence and threats of violence, there are criminalthreats and both arrangements are forms of crime. Thedif erence can be seen from the legal system, subject and object of rape, criminal sanctions, duration of criminalsanctions, and limitations of objects of rape. The results of his research show that regulations in Indonesia are considered to be far more complete and extensive regarding crimes against decency and are not limited to certainmatters, and to be able to provide a deterrent ef ect on perpetrators of rape, attentioncan be paid to punishment based onthe Law on Sexual Violence